2000
DOI: 10.1097/00007890-200004270-00010
|View full text |Cite
|
Sign up to set email alerts
|

Factor v R506q Mutation (Activated Protein C Resistance) Is an Additional Risk Factor for Early Renal Graft Loss Associated With Acute Vascular Rejection

Abstract: Renal transplant recipients who are carriers of the FV:Q506 allele have an increased risk of early graft loss. Vascular rejection changes including endothelialitis and fibrinoid vascular necrosis were more common in this group, and therefore an association between the hypercoagulable state, which entails an up-regulation of the mitogenic and proinflammatory enzyme thrombin, and the immunological challenge to the endothelium may be the cause of inferior prognosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
0
27
0
2
Order By: Relevance
“…As major reasons the occurrence of acute rejections, probably mostly vascular rejections, has been described (6,8,10). Furthermore, rates of early graft loss due to venous thromboembolism and graft perfusion defects were significantly elevated in patient groups tainted with thrombophilia (11).…”
mentioning
confidence: 99%
“…As major reasons the occurrence of acute rejections, probably mostly vascular rejections, has been described (6,8,10). Furthermore, rates of early graft loss due to venous thromboembolism and graft perfusion defects were significantly elevated in patient groups tainted with thrombophilia (11).…”
mentioning
confidence: 99%
“…Also FVL carriers had 12-fold higher risk of an early graft perfusion defect (Wuthrich, 2001). A higher risk of vascular rejection was found in FVL carriers, which was linked to the presence of endotheliolitis or fibrinoid necrosis on histopathology of renal grafts lost within the first year after transplant (Ekberg, 2000). The reported prevalence of prothrombin gene heterozygous mutation in renal transplant recipients is 3.7%, similar to that in the general population.…”
Section: Thrombophiliasmentioning
confidence: 82%
“…14 Ekberg and associates found that acute rejection in recipients with factor V R506Q mutation experienced early graft loss because of vascular rejection of the graft attributed to histologic changes including endotheliosis and fibrinoid vascular changes associated with FV genotype. 6 Studies have shown that recipients with hypercoagulable disorders have a significantly higher risk of early graft failure apart from thromboembolic events and acute rejection. 16 Long-term graft survival is higher when anticoagulants are administered prophylactically.…”
Section: Discussionmentioning
confidence: 99%
“…5 Early graft loss within the first year after transplant was 55.6%. 2,6 Delayed graft function and chronic graft dysfunction also have been reported.…”
Section: Introductionmentioning
confidence: 99%